1996
DOI: 10.1029/95wr02915
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Temperature Effects on Wetting Coefficients of Porous Solids and Their Capillary Pressure Functions

Abstract: We explored the notion that changes in wetting coefficients of porous solids contributed to the temperature sensitivities of capillary pressure functions (CPFs). A chemical-thermodynamic explanation for these contributions was developed. If the temperature sensitivities of CPFs were due to capillarity (i.e., due to temperature-induced changes in liquid-gas interfacial tensions or wetting coefficients), then for a given degree of saturation the ratios of capillary pressures to their temperature derivatives shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
162
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(165 citation statements)
references
References 21 publications
2
162
1
Order By: Relevance
“…This is quite different with some other studies that have been suggested that the capillary pressure decreases with elevated temperature. 31,36 The reason for this difference may be due to the fact that we impose a lower pressure for water at the bottom of the domain for elevated temperatures. This may lead to higher capillary pressures at earlier time steps.…”
Section: Effects Of Temperature On Dynamic Coefficientmentioning
confidence: 99%
See 2 more Smart Citations
“…This is quite different with some other studies that have been suggested that the capillary pressure decreases with elevated temperature. 31,36 The reason for this difference may be due to the fact that we impose a lower pressure for water at the bottom of the domain for elevated temperatures. This may lead to higher capillary pressures at earlier time steps.…”
Section: Effects Of Temperature On Dynamic Coefficientmentioning
confidence: 99%
“…Grant 31 The model takes into account the interfacial tension as a function of temperature. It was determined that the two-parameter model is better than the one-parameter model for a system with a larger temperature range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such case, expression of the infiltration process in terms of the diffusion equation (equation (7)) will not be appropriate since different points within the soil profile will follow different scanning curves, and there will be no unique relationship between gradients of and gradients of . Thermal effects will also induce significant changes in the estimated fluxes as temperature was found to affect soil hydraulic properties [Gardner, 1955;Philip and de Vries, 1957;Nimmo and Miller, 1986;Hopmans and Dane, 1986;Grant and Salehzadeh, 1996;Parlange et al, 1998;Grant and Bachman, 2002].…”
Section: Infiltration Under Special Conditionsmentioning
confidence: 99%
“…In many soil transport and hygrothermal problems, this is expressed as the combination of temperature effect in reference [8,9].…”
Section: Thermodynamic Relationshipmentioning
confidence: 99%